Arylamine N-acetyltransferases: a pharmacogenomic approach to drug metabolism and endogenous function. (1st June 2003) - Sim, E.; Pinter, K.; Mushtaq, A.; Upton, A.; Sandy, J.; Bhakta, S.; Noble, M.
Abstract : The arylamine N-acetyltransferases (NATs) are a unique family of enzymes that catalyse the transfer of an acetyl group from acetyl-CoA to the terminal nitrogen of hydrazine and arylamine drugs and carcinogens. The NATs have been shown to be important in drug detoxification and carcinogen activation, with humans possessing two isoenzymes encoded by polymorphic genes. This polymorphism has pharmacogenetic implications, leading to different rates of inactivation of drugs, including the anti-tubercular agent isoniazid and the anti-hypertensive drug hydralazine. Mice provide a good model for human NAT, allowing genetic manipulation of expression to explore possible endogenous roles of these enzymes. The first three-dimensional NAT structure was resolved for NAT from Salmonella typhimurium, and subsequently the structure of NAT from Mycobacterium smegmatis has been elucidated. These identified a 'Cys-His-Asp' catalytic triad (conserved in all NATs), which is believed to be responsible for the activation of the active site cysteine residue. As more genomic data become available, NAT homologues continue to be found in prokaryotic species, many of which are pathogenic, including Mycobacterium tuberculosis . The discovery of NAT in M. tuberculosis is particularly significant, since this enzyme participates in inactivation of isoniazid in the bacterium, with implications for isoniazid resistance. Structural studies on NAT proteins and phenotypic analyses of organisms (both mice and prokaryotes) following genetic modifications of the nat genes are leading to an understanding of the potentially diverse roles of NAT in endogenous and xenobiotic metabolism. These studies have indicated that NAT, particularly in Mycobacteria, has the potential to be a drug target. Combinatorial chemical approaches, together with in silico structural studies, will allow for advances in the identification of NAT substrates and inhibitors, both as experimental tools and as potential drugs.